A Retrospective Study on Therapeutic Efficacy of Transarterial Chemoembolization Combined With Immune Checkpoint Inhibitors Plus Lenvatinib in Patients With Unresectable Hepatocellular Carcinoma - Ying Teng; Xiaoyan Ding; Wendong Li; Wei Sun; Jinglong Chen (2022)
Objective: We assessed the efficacy and safety of transarterial chemoembolization (TACE) in combination with lenvatinib plus programmed death receptor-1 (PD-1) signaling inhibitors (camrelizumab or sintilimab) in unresectable hepatocellular carcinoma (uHCC). Methods: In this retrospective study, patients with uHCC were pretreated with lenvatinib for 1 to 2 weeks before TACE. Camrelizumab or sintilimab were initially administered intravenously in 1 week after TACE of a 21-day cycle. Primary objectives were objective response rate (ORR) and disease control rate (DCR) by modified Response Evaluation Criteria in Solid Tumors (mRECIST). The secondary endpoints included the progression-free survival (PFS), overall survival (OS), and toxicity. Results: Between March 5, 2019 and February 30, 2021, 53 patients were screened for eligibility. At data cutoff, 35.8% of patients remained on treatment. Median follow-up was 15.4 months. Confirmed ORR in the 51 evaluable patients was 54.9% (95% CI 41.4%-67.7%). DCR was 84.3% (95% CI 72.0%-91.8%). Median PFS was 8.5 months (95% CI 6.4 to 10.6 months). The median OS was not estimable. Grade ≥3 treatment-related adverse events occurred in 32.1% of patients. No new safety signals were identified. Conclusion: TACE in combination with lenvatinib plus anti-PD-1 inhibitors may have promising antitumor activity in uHCC. Toxicities were manageable, with no unexpected safety signals.